Theoretical analysis of the "green" synthesis of aniline by reduction of nitrobenzene. (16th January 2020) - Liu, Qi; Tadrent, Sarra; Proust, Christophe; Gomez, Francois; Khelfa, Anissa; Luart, Denis; Len, Christophe
Highlights: Method to investigate the possible chemical paths from thermodynamic considerations. New thermodynamic code (CIRCE) to deal with solids, liquids and vapors. Interpretation of experimental data from the reduction of nitrobenzene into aniline. Abstract: Recently a new chemical production means was proposed for producing aniline by reducing nitrobenzene in a much more environmentally friendly way (Tadrent et al., 2018). In particular, activated carbon and water are used instead of hydrogen on a metal catalyst without a precise detail of the process. In the present paper, a theoretical analysis is proposed based on a step by step thermodynamic examination of elementary reactions. It is found that the Haber mechanism is theoretically possible but that due to the size of the pores of the carbon, inside which the reduction occurs, only the smallest molecules can move so that the "direct" path is favored. This can explain why the yield is rather good.